How science works : everything you need to know about science in small, easily-digestible portions - Dinwiddie, Robert (Chartwell Books, 2014)
If your scientific knowledge is hazy and you want to keep up with the remarkable stories you’re seeing in the newspapers and on TV, this is the book for you. It will bring you up to speed in the hot areas of modern science, from atomic theory and the Big Bang to health scares and global warming. Bypassing complexities that only the scientists need to know, this book presents easy to follow sketches and summaries that drive home today’s most widely discussed scientific facts and theories. This book presents nine robust chapters, beginning with science basics – the building blocks of the world around us. Next, it gives you a closer look at the observable Universe, with a summary of how the world came into existence and a description of our planet and its environment. Subsequent chapters cover the human organism, our health, and our genes. A final chapter looks into astonishing far out topics in physics and cosmology, including the theory of relativity, string theory, and quantum theory. Illustrated and explained throughout with clear, colorful, down to earth analogies, and filled with truly amazing facts, this book will make you wonder why science wasn’t explained like this when you were in school